Creep Behavior and Deformation Mechanism of a Third-Generation Single Crystal Ni-Based Superalloy at 980 °C - Ruida Xu; Ying Li; Huichen Yu (Metals, 2023)
As the primary choice for aero-engine turbine blades, creep resistance is an important mechanical property for the developing third-generation single crystal Ni-based superalloys. The creep behavior of the superalloy in the [001] orientation was studied at 980 °C under a series of stress levels, accompanied with scanning electron microscope (SEM) and transmission electron microscope (TEM) observation to investigate the microstructure and deformation mechanism. The deformation mechanism of the alloy is found to be dislocation gliding, propagating and forming a dislocation network in the γ/γ′ interface. Dislocation networks could hinder the movement of dislocation and decrease the creep rate to a constant during the steady-creep stage. The formation of dislocation networks was analyzed due to the interaction of <110> {111} dislocations. Then dislocations cut into γ′ phases as individual <110> super-dislocations, anti-phase boundary dislocation pairs, and stacking faults. The <110> super-dislocation in the γ′ phase may cross-slip into the {001} plane from the {111} plane to form Kear–Wilsdorf locks, which could inhibit dislocations from gliding or cross-slipping and then enhance the creep resistance.